1985
DOI: 10.1016/s0006-3495(85)83775-9
|View full text |Cite
|
Sign up to set email alerts
|

Membrane structural domains. Resolution limits using diphenylhexatriene fluorescence decay

Abstract: Measurement of multiple fluorescence decay times of 1,6-diphenyl-1,3,5-hexatriene (DPH) in membranes can in principle be used to investigate structural domains of lipid bilayers. To assess the feasibility of this approach using phase and modulation techniques, we reduced experimental errors specifically associated with performing these measurements on membrane suspensions (probe self-quenching, background fluorescence, turbidity-induced artifacts) and determined empirically the level of precision thereby obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 31 publications
3
69
0
Order By: Relevance
“…The dose-dependent effect of cholesterol enrichment to decrease the initial rate of Na-Pi cotransport activity was paralleled by the dose-dependent effect of cholesterol enrichment to increase the steady-state fluorescence anisotropy of DPH, rDpH (Table IV). Analysis of the time-resolved fluorescence measurements indicated that the phase and modulation lifetimes exhibited a small deviation (< 5%) from a single-exponential decay, as is typically found for DPH in membrane systems above the lipid phase transition (25)(26)(27). The average lifetimes, 9.9 in control, vs. 10.0 in + 12% cholesterol, vs. 10.1 ns in +24% cholesterol, were not significantly different between the control and the cholesterol-enriched BBM.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The dose-dependent effect of cholesterol enrichment to decrease the initial rate of Na-Pi cotransport activity was paralleled by the dose-dependent effect of cholesterol enrichment to increase the steady-state fluorescence anisotropy of DPH, rDpH (Table IV). Analysis of the time-resolved fluorescence measurements indicated that the phase and modulation lifetimes exhibited a small deviation (< 5%) from a single-exponential decay, as is typically found for DPH in membrane systems above the lipid phase transition (25)(26)(27). The average lifetimes, 9.9 in control, vs. 10.0 in + 12% cholesterol, vs. 10.1 ns in +24% cholesterol, were not significantly different between the control and the cholesterol-enriched BBM.…”
Section: Resultsmentioning
confidence: 62%
“…The fluorescence lifetime of DPH was determined by time-resolved fluorescence measurements using a multifrequency phase and modulation fluorometer based on the Gratton design (23), as previously described (24). The measured phase and modulation values were analyzed assuming either that the decay was made up of a discrete sum of exponential components, or that the decay was made up of one or more continuous distributions of lifetime components (25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…Immunologic inhibition was determined using a monospecific polyclonal Ab (14,15) suspended in phosphate-buffered saline (PBS) with an activity of 0.6 U/Ml. 20 gl of brush border membrane vesicles (BBMV) were preincubated for 20 min at 20°C with varying amounts (0-20 ,l) of antibody solution, and the final volume was adjusted to 40 ,l using PBS (13).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments on small and large tmilamellar vesicles (SUV and LUV) indicate that curvature and water penetration can also explain the experimental results [13]. The temperature dependence of the lifetime in the two phases has been explained in term of water penetration and the enhancement of the decay from the second electronic state caused by the difference in the dielectric constant [7,10,14]. The basic idea is that the fluorescence lifetime of DPH is strongly influenced by the dielectric constant of the surrounding medium [9,15], although alternative explanations have been proposed [16].…”
mentioning
confidence: 91%
“…Using the fluorescent probe DPH (1,6-diphenyl-l,3,5-hexatriene), we have studied water penetration and membrane local structure in a variety of systems [1][2][3][4][5][6]. Although the DPH probe is generally used for determination of membrane order due to the preferential alignment of this probe along the lipid chains, several studies indicated that this probe also changes the fluorescence lifetime in different membrane environments [4,[7][8][9][10]. Typical lifetime values in the gel phase of the bilayer are in the 10-Laboratory for Fluorescence Dynamics, Department of Physics, University of Illinois at Urbana-Champaign, Urbana, Illinois 61801. z Istimto di Medicina Sperimentale, Viale Marx 15, 00137 Rome, Italy.…”
Section: Introductionmentioning
confidence: 99%